DYNAMICS OF THE MOVING RING-LOAD ACTING IN THE INTERIOR OF THE BI-LAYERED HOLLOW CYLINDER WITH IMPERFECT CONTACT BETWEEN THE LAYERS - Akbarov, S. D.; Mehdiyev, M. A.; Zeynalov, A. M. (INST APPLIED MATHEMATICS, 2021)
The dynamics of the moving-with-constant-velocity internal ring-load (-pressure) acting on the inner surface of the bi-layered hollow circular cylinder is studied within the scope of the piecewise homogeneous body model by employing the exact field equations of the linear theory of elastodynamics. It is assumed that the internal pressure is point-located with respect to the cylinder axis and is axisymmetric in the circumferential direction. Moreover, it is assumed that shear-spring type imperfect contact conditions on the interface between the layers of the cylinder are satisfied. The focus is on determination of the critical velocity with analyses of the interface stress distribution and their attenuation rules with respect to time. At the same time, there is analysis of the problem parameters such as the ratio of modulus of elasticity, the ratio of the cylinder's layers thickness to the external radius of inner layer-cylinder, and the shear-spring type parameter which characterizes the degree of the contact imperfection on the values of the critical velocity and stress distribution. Corresponding numerical results are presented and discussed. In particular, it is established that the values of the critical velocity of the moving ring-load increase with the thickness of the external layer of the cylinder.
Keywords: moving ring-load; critical velocity; bi-layered hollow cylinder; shear-spring type imperfection; interface stresses; COMPRESSIBLE VISCOUS-FLUID; HALF-SPACE; CRITICAL VELOCITIES; COVERING LAYER; CRITICAL SPEED; ELASTIC PLATE; SYSTEM; OSCILLATION; FIELD; Mathematics